Ketahanan Individu Pemuda Dengan HIV Serta Implikasinya Terhadap Demografi Indonesia - Lubis, Muhammad Zuchri Nasuha; Rofii, Muhammad Syaroni, Mr. (UI Scholars Hub, 2020)
This study analyzes the individual resilience of young HIV patients at the Teratai Clinic, Community Health Center, Kebayoran Lama District, South Jakarta City and influences it on Indonesian demographics. This study specifically aims to examine the condition of individual resilience of young HIV patients at the Teratai Clinic, Community Health Center, Kebayoran Lama District, South Jakarta City and the accompanying factors. Then the condition of individual resilience will have implications for the demographics of Indonesia. The method used is a qualitative method which is analyzed based on observations of the facts and phenomena found. Sources of data in this study are divided into primary and secondary sources. Primary data sources are in the form of interviews with respondents and direct observations of them. Secondary data sources are studies of related literature and documentation. The study uses the individual resilience theory popularized by Soemarno Soedarsono and an analysis of Indonesian demography using demographic variables studied by Hardiani. The results of this study indicate that three out of ten respondents have weak individual resilience (not strong) due to the lack of a place to tell stories and are prone to experiencing mood swings. Starting from worrying about his health, production period and sins committed in the past. Their individual resilience also has an impact on Indonesia's demographics. At birth rates, in general, couples who are infected with HIV and are not on ARV therapy will choose not to have children for fear of transmitting the disease to their partners and children. Regarding the death rate, this can be seen from FM. He died because he did not care about his condition which had been infected with HIV. Population mobility is also affected. Many people avoid living in the capital and other big cities which are likely to be influenced by promiscuity and will increase the rate of HIV transmission